Jefferson Davis, unconquerable heart - Allen, Felicity, 1924- (Shades of blue and gray series., 1999)
The author begins the story "with Davis's political imprisonment at the end of the Civil War and ... flashes back to his earlier life, interweaving Davis's private life as a schoolboy, a Mississippi planter, a husband, a father, and a political leader. She follows him from West Point through army service on the frontier, his election to the U.S. House of Representatives, his regimental command in the Mexican War, his service as U.S. secretary of war and senator, and his term as president of the Confederate States of America."--Jacket.